Autologous Gluteal Augmentation with Parasacral Perforator-Pedicled Propeller Flaps. Issue 6 (5th April 2022) - Bekara, Farid; Chaput, Benoit; Ciucur, Elena; de Boutray, Marie; Boccara, David; Bertheuil, Nicolas; Herlin, Christian
Abstract : Background: De-epithelialized flaps have been used in gluteal contouring over the last three decades, but most improve the projection rather than the upper quadrants. The authors provide a detailed description of their method of gluteal augmentation using parasacral perforator-pedicled propeller flaps. This technique achieves a volumetric increase and maximal buttock projection at the midlevel and in the medial half of the buttocks. Methods: Between January and December of 2019, a series of 18 patients on whom a lower body lift with a parasacral perforator-pedicled propeller flap had been performed by the senior author (F.B.) were prospectively evaluated. Postoperatively, the satisfaction rate was assessed using a 10-point analog scale (1 = unsatisfied, 10 = very satisfied) by the patient and by two independent surgeons based on photographs taken 1 year after surgery. Results: Eighteen patients underwent this procedure. Their mean age was 32.2 ± 5.6 years (range, 24 to 40 years). The mean flap length was 20.3 cm, their mean width was 10.4 cm, and the mean thickness was 3.4 cm. The authors noted only two minor complications, one seroma and two skin dehiscences that healed without surgery. The rate of satisfaction as assessed by the patients was 8.3 out of 10 (±1.1), and by surgeons, 7.9 and 8.1. Conclusion: This article describes a gluteal autoaugmentation flap technique using parasacral perforator-pedicled propeller flaps to increase projection and volume in the inferomedial gluteal region after lower body lift. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.